Discipline and Punish / The Birth of the Prison - Foucault Michel (Penguin Books, 1979)
The writer in this book shows in fascinating detail the development of the Western System of prisons, police organizations, administrative and legal hierarchs for social control - and the growth of disciplinary society as a whole. Torture, The Body of the Condemned, The Spectacle of the Scaffold, Punishment, Generalized Punishment, The Gentle Way in Punishment, Discipline, Docile Bodies, The Art of Distributions, The Control of Activity, The Organization of Geneses, The Composition of Forces, The Means of Correct Training, Hierarchical Observation, Normalizing Judgement, The Examination, Panopticism, Complete and Austere Institutions, Illegalities and Delinquency, The Carceral, Notes, Bibliography.